The Intracellular Loop 2 F328S Frizzled-4 Mutation Implicated in Familial Exudative Vitreoretinopathy Impairs Dishevelled Recruitment. (24th November 2015) - Pau, Milly S.; Gao, Shujuan; Malbon, Craig C.; Wang, Hsien-yu; Bertalovitz, Alexander C.
Familial exudative vitreoretinopathy (FEVR) is a disease state characterized by aberrant retinal angiogenesis. Norrin-induced activation of Frizzled-4 (Fz4) has a major role in regulating beta-catenin levels in the eye that, in turn, modulate the blood retina barrier (BRB). Here we gain insight on the basis of the pathology of a FEVR implicated F328S Fz4 mutant by study. The receptor exhibits a substantially reduced ability to activate Lef/Tcf-dependent transcription. This impaired activation correlates with a decreased ability to stabilize and recruit Dishevelled-2 (Dvl2) to the cell surface. Aromaticity at position 328 of the intracellular loop 2 (iloop2) is revealed similarly as a prerequisite for Dvl2 recruitment to the Fz4. This aromaticity at 328 enables normal Norrin-induced canonical activation. The corresponding position in iloop2 of other Frizzleds likely functions in Dvl recruitment.